Reconceptualizing Arabic language curriculum quality: a standards-based evaluation of the grade eight curriculum in Arabic schools in Brunei Darussalam - Yani, Achmad; Haji Ahmad, Siti Sara; Haji Abdullah, Hajah Rafidah; Mohamed Abdelgelil, Mohamed Fathy; Seff, Faisal Mubarak; Sahrir, Muhammad Sabri; Haji Abdul Kahar, Kujaimah; Haji Abdullah, Hajah Rafizah; Mohamed Mousa, Abdelnaser Abdelgalil; Husain, Muhammad Zakir (WSEAS Press, 2026)
This study evaluates the content of the Arabic language curriculum prescribed for Grade Eight students in Arabic schools in Brunei Darussalam in light of international standards for language education. It seeks to determine the extent to which the curriculum aligns with principles of communicative competence and contemporary curriculum design quality. The study employed a descriptive-analytical evaluative approach within a mixed-methods research design, integrating quantitative and qualitative data. Questionnaire responses were analyzed through weighted percentages and descriptive statistics, while findings were interpreted in the light of semi-structured interviews, document analysis, and classroom observations, following the principle of methodological triangulation to enhance credibility and interpretive depth (Cohen et al., 2018, pp. 287–314; Johnson & Onwuegbuzie, 2004, pp. 14–26). The study sample consisted of Arabic language teachers responsible for teaching Grade Eight in Arabic schools in Brunei Darussalam. The findings indicate that the curriculum demonstrates an acceptable to good level of pedagogical and linguistic adequacy. It is broadly appropriate to students’ linguistic and developmental levels and exhibits considerable strength in lexical and grammatical organization, particularly in supporting reading comprehension and sentence construction. However, the results also reveal a relative imbalance in the distribution of language skills, with reading and writing more strongly represented than listening and speaking, while the effective enactment of oral skills depends heavily on teacher initiative (Richards, 2013, pp. 5–33; Canale& Swain, 1980, pp. 1–47). The study further found that the curriculum privileges Islamic and Arab cultural content more than local Bruneian sociocultural realities, and that morphology and learner differentiation remain comparatively underdeveloped. Accordingly, the study recommends strengthening skill balance, redesigning morphological progression, and expanding the representation of local cultural context in accordance with contemporary principles of materials development (Tomlinson, 2012, pp. 143–179)